1999
DOI: 10.1109/49.772439
|View full text |Cite
|
Sign up to set email alerts
|

IP-address lookup using LC-tries

Abstract: There has recently been a notable interest in the organization of routing information to enable fast lookup of IP addresses. The interest is primarily motivated by the goal of building multigigabit routers for the Internet, without having to rely on multilayer switching techniques. We address this problem by using an LC-trie, a trie structure with combined path and level compression. This data structure enables us to build efficient, compact, and easily searchable implementations of an IP-routing table. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
187
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(188 citation statements)
references
References 22 publications
0
187
0
1
Order By: Relevance
“…Some of them compress the trie for decreasing the memory consumption and improving the speed [1][2], [19][20][21]. Since a binary trie needs lots of comparisons and memory accesses, many solutions use multibit trie concept to accelerate the lookup search [3][4][5][6][7][8][9][10][11][12][13]; however, using a multi-bit trie instead of binary trie normally increases the memory consumption. Some papers have proposed compression methods for solving this problem [8]- [13].Compression methods usually suffer from update overhead.…”
Section: E Related Workmentioning
confidence: 99%
“…Some of them compress the trie for decreasing the memory consumption and improving the speed [1][2], [19][20][21]. Since a binary trie needs lots of comparisons and memory accesses, many solutions use multibit trie concept to accelerate the lookup search [3][4][5][6][7][8][9][10][11][12][13]; however, using a multi-bit trie instead of binary trie normally increases the memory consumption. Some papers have proposed compression methods for solving this problem [8]- [13].Compression methods usually suffer from update overhead.…”
Section: E Related Workmentioning
confidence: 99%
“…Level compressed tries. Nilsson and Karlsson [48] made a sensation when they discovered the "LC trie" (in full: Level Compressed trie): they demonstrated that their data structure could handle address lookup in routing tables with a standard PC in a way that can compete favorably with dedicated hardware embedded into routers. One of their beautifully simple ideas consists in compressing the perfect tree contained in a trie (starting from the root) into a single node of high degreethis principle is then used recursively.…”
Section: The Size (2 H ) Of the Extendible-hashing Index Is On Averagmentioning
confidence: 99%
“…It is evocative of a partial realization of extendible hashing. The decisive advantage in terms of execution time stems from the fact that chains of pointers are replaced by a single array access, while the search depth decreases to O(log log n) for a large class of distributions [12,13,48] …”
Section: The Size (2 H ) Of the Extendible-hashing Index Is On Averagmentioning
confidence: 99%
“…For w bits IP addresses, the main drawback of this structure is its worst case O(w) node access complexity for search and update procedures. Some improvements of Trie [2]- [4], were also introduced to solve this problem. However, most of them suffer from the above disadvantage or time consuming update procedures.…”
Section: Introductionmentioning
confidence: 99%